2002
DOI: 10.1093/toxsci/67.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Mechanism of Cinnabar and Mercuric Sulfide on the Vestibulo-Ocular Reflex System of Guinea Pigs

Abstract: Cinnabar, a naturally occurring mercuric sulfide (HgS), has been combined with Chinese herbal medicine as a sedative for more than 2000 years. To date, its neurotoxic effect on the vestibulo-ocular reflex (VOR) system has not been reported. By means of a caloric test coupled with electronystagmographic recordings, the effect of commercial HgS and cinnabar on the VOR system of guinea pigs was studied. HgS or cinnabar was administered orally (1.0 g/kg) to Hartley-strain guinea pigs once daily for 7 consecutive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…In comparison, the ototoxicity produced by methyl mercury was so dramatic and irreversible, even at doses 1/1000 to 1/5000 of cinnabar (24)(25)(26)(27)(28)(29). It should also be pointed out that the dose of cinnabar or mercury sulfide (1.0 g/kg) used in these studies is at least 100-500 times higher than human daily dose (i.e., 50 g/50 kg person, while allowable daily human oral dose is 0.1 -0.5 g) (1).…”
Section: Toxicological Profiles Of Cinnabar Mercury Vapor Mercuric mentioning
confidence: 98%
See 1 more Smart Citation
“…In comparison, the ototoxicity produced by methyl mercury was so dramatic and irreversible, even at doses 1/1000 to 1/5000 of cinnabar (24)(25)(26)(27)(28)(29). It should also be pointed out that the dose of cinnabar or mercury sulfide (1.0 g/kg) used in these studies is at least 100-500 times higher than human daily dose (i.e., 50 g/50 kg person, while allowable daily human oral dose is 0.1 -0.5 g) (1).…”
Section: Toxicological Profiles Of Cinnabar Mercury Vapor Mercuric mentioning
confidence: 98%
“…In comparison to methyl mercury, oral cinnabar or mercury sulfide administration results in at least 1000-fold less tissue mercury accumulation in mice (24)(25)(26)(27), and in rats (28). Synthetic mercury sulfide was reported to have better bioavailability than cinnabar in mice (18,21), but in other studies, synthetic mercury sulfide was reported to have less oral bioavailability than cinnabar in mice (27) and in guinea pigs (29). This discrepancy could be due to differences in cinnabar processing methods, as well as to animal species or strain variation.…”
Section: Absorptionmentioning
confidence: 98%
“…57 Taken orally HgS can be toxic; high doses in rodents (1.0 g/kg) have been associated with hearing loss, memory, and behavioral problems with long-term administration causing gastrointestinal symptoms, renal dysfunction, and blurred vision. [58][59][60] While not considered to cross the blood-brain barrier or placenta, a small portion of HgS can be reduced in the tissues and exhaled as Hg vapor with accumulation in the cerebral cortex and cerebellum. 56,61 In the current study, Hg in TM was taken at doses far below those associated with HgS toxicity, while Hg in blood and urine (the latter detected in only 20% of patients) were well below international safety levels.…”
Section: Sallon Et Al Mercury In Tibetan Medicine 327mentioning
confidence: 99%
“…The shocked world of Minamata disease was caused by mercury poisoning in Japan in 1956. It is universally acknowledge that mercury and its compounds exhibit highly chronic toxicity [3] , which has threaten to our kidneys, the central nervous system and the reproductive system [4][5][6][7][8][9][10]. Hence, mercury was strictly limited applied to medicine in international society, which not only affect the medicine export but also damage to the reputation of traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%